Outcome of children with newly diagnosed acute lymphoblastic leukemia treated with CCLG‐ALL 2008: The first nation‐wide prospective multicenter study in China. Issue 7 (15th May 2018) - Cui, Lei; Li, Zhi‐Gang; Chai, Yi‐Huan; Yu, Jie; Gao, Ju; Zhu, Xiao‐Fan; Jin, Run‐Ming; Shi, Xiao‐Dong; Zhang, Le‐Ping; Gao, Yi‐Jin; Zhang, Rui‐Dong; Zheng, Hu‐Yong; et al.
Abstract : Acute lymphoblastic leukemia (ALL) is the most common malignancy among children. The trial Chinese Children Leukemia Group (CCLG)‐ALL 2008 was a prospective clinical trial designed to improve treatment outcome of childhood ALL through the first nation‐wide collaborative study in China. Totally 2231 patients were recruited from ten tertiary hospitals in eight cities. The patients were stratified according to clinical‐biological characteristics and early treatment response. Standard risk (SR) and intermediate risk (IR) groups were treated with a modified BFM based protocol, and there was 25%‐50% dose reduction during intensification phases in the SR group. Patients in high risk (HR) group received a more intensive maintenance treatment. Minimal residual disease (MRD) monitoring with treatment adjustment was performed in two hospitals (the MRD group). Complete remission (CR) was achieved in 2100 patients (94.1%). At five years, the estimate for overall survival (OS) and event‐free survival (EFS) of the whole group was 85.3% and 79.9%, respectively. The cumulative incidence of relapse (CIR) was 15.3% at five years. The OS, EFS and CIR for the SR group were 91.5%, 87.9%, and 9.7%, respectively. The outcome of the MRD group is better than the non‐MRD group (5y‐EFS: 82.4% vs 78.3%, P = .038; 5y‐CIR: 10.7% vs 18.0%, P < .001). Our results demonstrated that the large‐scale multicenter trial for pediatric ALL was feasible in China. Dose reduction in the SR group could achieve high EFS. MRD‐based risk stratification might improve the treatment outcome for childhood ALL.